PENGEMBANGAN MEDIA ONLINE DI PONDOK PESANTREN TARBIYATUL ISLAM AL FALAH KOTA SALATIGA - Saipullah Hasan; Avin Wimar Budiyastomo; Vina Fellinda Alfiatun Maghfiroh (Universitas Kristen Satya Wacana Salatiga, 2022)
Tarbiyatul Islam Al Falah Islamic Boarding School has a significant role in shaping the character and skills of the students. This can be seen from the educational model that is carried out not only around religion but also in providing social services in developing the potential of the students. The service method uses an asset-based community development (ABCD) approach. Through the ABCD approach, the students are directed to develop their potential with their media use skills. The purpose of this study was to find out how the development of online media by Islamic boarding schools in improving the ability of students to access information technology. The online media training for students showed participation, interest, and talent to develop their skills in the use of online media.